Applying Cooperative Learning Using the Number Head Together Method in Teaching Balaghah - Muna Ashila; Syahminan Syahminan; Muhammad Ridha; Abdullah Abdullah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Based on initial observations made by researcher at Dayah Modern Darul Ulum Banda Aceh, researcher found that students consider Balaghah as one of the most difficult subjects, and most students do not master a lot of vocabulary in the book, and this makes students feel bored and do not want to learn it so that the material is not well understood. This study aims to determine the effectiveness of the application of cooperative learning approach with Numbered Head Together model to improve students' ability to understand Balaghah and to know the activities of teachers and students when applying cooperative learning approach with Numbered Head Together model in teaching Balaghah. The research method used by researchers is the experimental method with the